Contents and stocks of soil organic carbon in different types of land use in the Southern Plateau of Santa Catarina (Brazil) - Santos, Kristiana Fiorentin dos; Barbosa, Fabrício Tondello; Bertol, Ildegardis; Werner, Romeu de Souza; Wolschick, Neuro Hilton; Mota, Josie Moraes (Revista de Ciências Agroveterinárias, 2019)
The study of soil carbon changes caused by the land use alteration allows adopting measures to reduce the risk of future negative impacts. This study aimed to quantify and compare the contents (TOC) and stocks (SOC) of total organic carbon for different types of land use in the southern Plateau of Santa Catarina. The areas selected were natural forest (NF), planted pine (PP), natural rangeland (NR), and crops in succession with pasture (CSP). Soil samples were collected at depths of 0-5, 5-10, 10-20, and 20-40 cm, where the TOC were determined and the SOC were calculated by two methods, one considering the equivalent soil layer and the other the equivalent soil mass. The different types of land use influence the TOC and SOC, which are higher in the NF. The TOC values were, respectively 33.9; 27.1; 26.0, and 23.2 g kg-1 for NF, PP, NR and CSP, in the soil layer average of 0-40 cm. The EC values up to the depth of 40 cm were respectively 121.5; 113.8; 112.4, and 100.6 Mg ha-1, based on the equivalent soil layer, and 121.5; 102.2; 99.1 and 89.8 Mg ha-1 after correction for the equivalent soil mass. Proper management of land use, recovery of forests and afforestation of lands are important steps to allow carbon sequestration in the soil.